(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The recognition and prestige of a company engaged in distribution logistics significantly increases the efficiency of business activities of manufacturing enterprises. The purpose of the article is to generalize and clarify certain theoretical and applied aspects of distribution, distribution channels, their coordination, meeting the needs of customers and identifying the importance of distribution logistics for increasing the efficiency of business activity. It was determined that distribution logistics are processes that are carried out to ensure the efficient movement of finished products from the manufacturer to the consumer. It includes: transportation of goods, warehousing, material handling, packaging, insurance, inventory control, location selection of enterprises and warehouses, order processing, marketing forecasts and customer service. It was established that the strategy of a business entity in the distribution system represents a generalized system of conceptual approaches, rules, and interrelated functions aimed at optimal distribution of product flows between channels and links of product promotion and effective realization of product resources. Companies can use one of four distribution strategies: direct, intensive, selective, and exclusive. It is proven that effective distribution channels are created when no other group of enterprises provides a higher profit or lower costs per unit of production, or a higher level of consumer satisfaction. Modifications in the structure of distribution channels occur in three possible directions - outsourcing, postponement and situational actions. The following delivery options are possible in the physical distribution system: cross docking system, milkman’s route and value-added logistics (VAL). It is justified that the customer receives a certain standard of service together with the product. The customer service system includes elements of logistics (access to goods), marketing (satisfaction of needs) and finance (terms and forms of payment). In order to ensure the constant availability of products and minimize operational costs, enterprises must rationally manage stocks. They use the following inventory management methods: ABC, XYZ or their combination, the optimal economic order quantity - EOQ, inventory control models, materials requirements planning systems - MRP, distribution requirements planning - DRP, "just in time" system - JIT. The choice of inventory control method is influenced by the following factors: assortment structure of materials, terms of order fulfillment, periodicity of supply, storage methods and types of material consumption flows.